English Pronunciation Errors Made by Saudi Students - Islam Ababneh (European Scientific Journal, ESJ, 2018)
Arabs often pronounce many English words wrongly which leads to spelling and writing errors. This paper deals with English pronunciation errors made by two groups of native Saudi Arab speakers. The students in the first group are of English major while the students in the second group are of Arabic major. Generally, Arabic speakers use direct transfer and interference from Arabic in addition to stress shifts in their pronunciation that are not recognized stress patterns in English. Also, there are some sounds in English that have no equivalence in Arabic, which leads to vowel and consonant errors. This study identifies the pronunciation errors made by Saudi students in pronouncing words of problematic nature to Arabs in general. The students in both groups made vowel insertion and confusion, orthography, stress, intonation, errors; but the more trained students in group 1 made less errors than the students in group 2.